Pengaruh Pengembangan Karir, Lingkungan Kerja, dan Digital Engagement terhadap Kinerja Karyawan pada PT BPR BKK Boyolali: (Studi Kasus pada Karyawan PT BPR BKK Boyolali) - Muhammad Abiyyu Al Hammam; Unna Ria Safitri; Alean Kistiani Hegy Suryana; Fathimah Tsabitah Al-Khairiyah (Jurnal Manajemen Riset Inovasi, 2026)
This study aims to analyze the influence of career development, work environment, and digital engagement on employee performance at PT BPR BKK Boyolali. This research uses a quantitative approach with a survey method involving 100 employees as respondents. The sampling technique applied is saturated sampling, where all members of the population are included as research samples. Data were collected through questionnaires and documentation, then analyzed using SPSS with multiple linear regression analysis. The results indicate that career development, work environment, and digital engagement simultaneously have a positive and significant effect on employee performance. Partially, career development and work environment have a positive and significant influence on employee performance, while digital engagement does not show a positive effect on employee performance at PT BPR BKK Boyolali. The coefficient of determination test (R²) shows that the three independent variables contribute 51.6% to explaining variations in employee performance, while the remaining 48.4% is influenced by other factors outside the research model. These findings highlight the importance of career development and a supportive work environment in improving employee performance.